Comparisons of the characteristics of partial nitrification sludge exposed to CuO nanoparticles combined with different antibiotics. Issue 6 (December 2021) - Zhang, Xiaojing; Zhang, Hongli; Wei, Denghui; Chen, Zhao; Zhang, Nan; Ma, Yongpeng
Abstract: Nanoparticles (NPs) and antibiotics are currently two of the main emerging pollutants that can significantly impact wastewater treatment processes. In this study, the joint effects of CuO NPs with the antibiotic sulfamethoxazole (SMX) or oxytetracycline (OTC) on partial nitrification (PN) sludge were investigated. After long-term exposure, the gene transcripts abundance of aerobic ammonia-oxidizing bacteria (AOB), specific AOB activity (SAA), and extracellular polymers (EPS) were detected and compared. Both CuO NPs+SMX and CuO NPs+OTC treatment exhibited severe inhibition of the PN sludge, which ultimately decreased SAA to 2.693 (±0.127) and 3.710 (±0.099) mg g −1 SS h −1 from 5.372 mg g −1 SS h −1 under the control conditions, while AOB abundance was 0.622 (±0.071) and 0.817 (±0.088), respectively. EPS, which is a pre-indicator of the reactor performance, was the key factor that enabled the PN sludge in resisting NPs and antibiotics, but the recovery ability of PN sludge after the stress was poor. Graphical Abstract: ga1 Highlights: Joint CuO NPs+SMX gradually decreased SAA by 50.1% after 30 days' exposure. Joint CuO NPs+OTC sharply decreased SAA by 30.8% after 10 days' exposure. PN sludge suffered CuO NPs+OTC showed better resistance and recovery performance. CuO NPs+SMX and CuO NPs+OTC decreased amoA gene to 62.2% and 81.7%, respectively. EPS was the key factor help PN sludge resisting the joint inhibitors.